Self-disturbance in first-episode psychosis: Theoretical framework and potential cannabis interactions - a systematic review - Ricci, Valerio; De Berardis, Domenico; Martinotti, Giovanni; Maina, Giuseppe (Frontiers in Psychiatry, 2026)
Cannabis use represents a significant environmental risk factor for psychotic disorders, with emerging evidence suggesting complex interactions between cannabinoid exposure, dissociative experiences, and fundamental disturbances of self-experience (self-disorders) in early psychosis. This systematic review examines the phenomenological and neurobiological relationships among dissociation, cannabis use, and self-disturbance in first-episode psychosis (FEP) patients. Following PRISMA guidelines, we conducted a comprehensive search of four databases (PubMed, Scopus, PsycINFO, Web of Science) from January 1990 to September 2025, identifying 22 studies meeting inclusion criteria (total N = 3,847 participants). Results demonstrate that cannabis use, particularly high-potency THC products, is consistently associated with significantly elevated dissociative experiences compared to non-using FEP patients. Across studies employing the Dissociative Experiences Scale-II (DES-II), cannabis users showed score elevations of 11–13 points, exceeding clinically significant thresholds and persisting at follow-up assessments. Daily high-potency cannabis use was associated with three-fold increased odds of clinically significant dissociation (OR: 3.21, 95% CI: 2.14-4.82) and more severe anomalous self-experiences compared to non-using patients. Multiple mechanisms mediate these relationships: alterations in CB1 receptor availability and endocannabinoid system dysregulation in regions critical for self-awareness, disruption of neural networks supporting minimal self-consciousness, and acute psychotomimetic effects including depersonalization and derealization that may persist beyond intoxication periods. Cannabis-related dissociation shows distinct phenomenological characteristics compared to primary dissociative disorders, with greater self-world boundary confusion and more severe distortions of first-person perspective. Longitudinal studies indicate that persistent dissociative symptoms and self-disorders in cannabis-using FEP patients predict poorer functional outcomes (12-month GAF scores: 52 ± 14 vs. 67 ± 12 in non-users, p<0.001) and increased symptom chronicity. However, approximately 75% of patients showed dissociation reduction following cannabis cessation, suggesting potential reversibility. GRADE certainty of evidence was rated as moderate for dissociative symptom severity (downgraded for observational study designs) and low for self-disturbance outcomes (limited direct evidence with EASE assessment). This review highlights the importance of comprehensive phenomenological assessment in cannabis-using FEP patients, incorporating dissociative symptomatology and basic self-disturbance evaluation, with implications for early intervention strategies and targeted therapeutic approaches. Future research should employ longitudinal designs with repeated phenomenological assessments, biological verification of cannabis exposure, and integration of neuroimaging with experiential measures to elucidate causal mechanisms.